Sequential PET/CT and pathological biomarker crosstalk predict response to PD-1 blockers alone or combined with sunitinib in propensity score-matched cohorts of cancer of unknown primary treatment - Wang, Youlong; Huang, Qi; Zhong, Guanqing; Lv, Jun; Guo, Qinzhi; Ma, Yifei; Wang, Xinjia; Zeng, Jiling (Frontiers in Oncology, 2023)
Immune checkpoint inhibitors (ICIs), including toripalimab and pembrolizumab, have not been testified in treatment of cancer of unknown primary(CUP), which has a very poor prognosis. Combined with anti-angiogenic therapies, ICIs are hypothesized to be effective in prolonging overall survival. The study aims to give evidence on the treatment effects of sunitinib combined with ICIs, find pathological biomarkers associated with changes in volumetric 18F FDG PET/CT parameters, and interrogate inner associations among these markers associated with response on PET/CT.The study recruited patients receiving combined treatment (ICIs + sunitinib) and compare the effects with separate treatment and with age-matched negative controls, analyzed in propensity score-matched (PSM) pairs. Markers associated with survival were identified and their inner associations were tested with structural equation modeling.A total of 292 patients were enlisted in the final analysis with 53 patients receiving combined treatment. Survival analysis demonstrated significantly prolonged survival in either combined or separate treatment, with the combined arm showing better response when PSM-paired by pre-treatment whole-body PET/CT parameters. Angiogenic marker KDR and VEGF mediates the PD-1 blockade impact on volumetric value changes, in positive and negative manners, respectively.Anti-angiogenic agents sunitinib may potentiate PD-1 blockade by diminishing angiogenesis or its downstream effects. The combined separate treatment increased survival of CUP patients and the responses could be evaluated by volumetric PET/CT parameters.